THE ROLE OF THE CIRCULAR ECONOMY IN A COUNTRY’S INDUSTRIAL SECTOR - Qodirova , Dilnura; Saitov , Sirojiddin (Scientific practical conference, 2026)
This thesis examines the concept of the circular economy, its core principles, and its strategic role in the development of national industry. In the context of increasing resource scarcity, environmental degradation, and the limitations of the traditional linear economic model, the circular economy is considered an effective mechanism for ensuring sustainable industrial development. The study analyzes the economic, environmental, and social benefits of efficient resource use, waste reduction, recycling, and reuse within industrial sectors. In addition, international best practices and the possibilities of adapting them to national industrial development are discussed.